2016
DOI: 10.1027/1866-5888/a000164
|View full text |Cite
|
Sign up to set email alerts
|

Does Authentic Leadership Predict Employee Work Engagement and In-Role Performance?

Abstract: Abstract. This study sought to examine whether and why authentic leadership predicts followers’ in-role performance and did so in a four-wave, multi-level, multi-source field study conducted in the banking sector in Pakistan. Working from the notion that authentic leadership fosters followers’ focus on developing their true self; we suggest authentic leadership predicts followers’ learning goal orientation. Given that learning goal orientation strongly impacts on how people approach and experience their work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…Leaders can influence employee work engagement not only through changing work conditions but also directly through inspiring, connecting, and strengthening their employees (Schaufeli, 2015). In addition, several positive leadership styles have been linked to employee work engagement in longitudinal studies (Biggs et al, 2014; Chughtai et al, 2014; Fletcher, 2016; Li and Liao, 2014; Mehmood et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaders can influence employee work engagement not only through changing work conditions but also directly through inspiring, connecting, and strengthening their employees (Schaufeli, 2015). In addition, several positive leadership styles have been linked to employee work engagement in longitudinal studies (Biggs et al, 2014; Chughtai et al, 2014; Fletcher, 2016; Li and Liao, 2014; Mehmood et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several longitudinal studies have shown that different positive leadership styles act as an antecedent of work engagement, for example, ethical leadership (Chughtai et al, 2014), authentic leadership (Mehmood et al, 2016), and transformational leadership (Salanova et al, 2011). Moreover, positive leadership styles have been shown to enhance employees’ engagement not only directly but also indirectly through increasing job resources and decreasing job demands (Schaufeli, 2015; Schaufeli and Bakker, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Stander et al [51] suggested that when leaders show authenticity, their employees are more optimistic and have more trust in the organization, which ultimately leads to higher work engagement. Research findings indeed revealed that authentic leadership increases work engagement among employees and their job performance [52,53]. Furthermore, there is a positive relationship between authentic leadership, as rated by employees, and employees’ work engagement [54].…”
Section: Introductionmentioning
confidence: 99%
“…Organization as a whole and individual in particular contributes towards improved job performance. [1] The growing trends and increased competition in hospitality and tourism industry has caused even the front runners of the industry to evaluate their practices and check for areas of improvement.…”
Section: Introductionmentioning
confidence: 99%